Performance Analysis Of A Compliant Wing For A Light Aircraft - Mohamad Sidik, Mohamad Sabri (Universiti Sains Malaysia, 2005)
Main purpose of this project is to apply the compliant mechanism into aircraft wing. It can improve the flight performance of conventional light aircraft. A compliant mechanism is flexible structure that elastically deforms without joints to produce a desired force or displacement. This study was precisely to analyze a compliant mechanism that has to be fitted to the leading edge of aircraft Beech King Air C90B wings. An innovation by Prof. Sridhar Kota creates compliant which can change wing leading edge angle from 0º until 6º. This design created using topology optimization method. With help of ANSYS software, leading edge structure for conventional light aircraft will be optimizing until gaining the most suitable shape in certain condition. Analysis will able to prove the design improving the flight performance for conventional light aircraft. It focused on its computational fluid dynamic analysis in determining the value of lift coefficient and drag coefficient using FLUENT 6.0 software. Expected result through this analysis is it should be a different in value of lift coefficient and drag coefficient when applying different angle of leading edge. It should increase the lift and drag forces due to respect angle of attack.